Intensive Versus Non Intensive Arabic - Sami Hanna (Al-Lisaniyyat)
his study attempts to find out if there is any difference between American students who study Arabic for one year and those who study the same course in eight weeks which is called « intensive ». It also attemps to find out whether or not there is a correlation between the student’s language learning aptitude and his /her achievement in the regular and intensive course. The experiment was conducted at the University of Utah- The subjects of the experiment are American students who enrolled in the first year Arabic and students who took the same course in eight weeks only. Comparing the scores of each group it was found a slight superiority of the regular students. It was found that there is a high correlation between the Modern Language Apti tude Test (MLAT) and the achievement of the students in both groups.